Pengaruh Level Tepung Jagung Terhadap Kualitas Organoleptik, Oksidasi Lemak Dan Total Bakteri Sui Wu’u Daging Babi Bagian Perut - Gradiana Usolin, Maria; Sulmiyati, Sulmiyati; M. Sipahelut, Geertruida; E. M. Malelak, G. (Green Publisher Indonesia, 2024)
The purpose of this study was to determine the effect of corn flour levels on organoleptic quality, fat oxidation and total bacteria in the processing of pork belly sui wu'u. This study used a Complete Random Design (RAL) consisting of three treatments and five replicates so that there were 15 experimental units. The pork used were: belly pork including fat and skin as much as 250 g from each test, and the use of cornmeal with different levels in each treatment, namely: 200% (P1), 400% (P2), and 600% (P3). The variables measured were fat oxidation, total bacteria and organoleptic tests including color, aroma, taste and texture. The results of statistical analysis showed that the administration of corn flour with different levels in sui wu'u of abdominal pork showed a real effect (P<0.05) on organoleptic quality and TBA value, but no real effect (P>0.05) on TPC. It was concluded that the higher the level of corn flour given, the higher the organoleptic quality and the decrease in Total Plate Count (TPC). The best level of cornstarch in pork sui wu'u is at the level of 600%. The best organoleptic quality is: color at P3 2.70±1.15% (pale red), the best value of TBA at P2 is 12.81±1.08 mg. Mal/g, and the best value of TPC in P2 is 3.37±3.38 (colony/gr).